Incentivos fiscais do ICMS e as importações dos estados brasileiros: impactos da resolução do senado federal nº 13/2012 sobre a guerra fiscal dos portos - Lima, Gerlene Eugenia Melo de (2017)
One of the modalities of the Fiscal War is the so-called "War of the Ports", which consists in the concession of ICMS tax incentives on the importation of goods originating in other countries, as well as ICMS on the interstate operation of these products, in order to attract investments and promote the flow of imports and collection of ICMS to the State that grants the incentive. With the aim of ending the "War of the Ports" and increasing the competitive capacity of national production, Federal Senate Resolution 13/12 was published, effective as of 2013. This work seeks to verify if said legal measure has brought in fact, some result in the fight against the "War of the Ports", from the analysis of the values of the imports destined for the States of Amazonas, Pará, Bahia, Ceará, Pernambuco, Goiás, Rio Grande do Sul, Santa Catarina, Paraná, Gerais, Rio de Janeiro and São Paulo, and the collection of ICMS from the states of Ceará and Espírito Santo. The results showed that the mentioned legal measure was only significant for the import of five of the studied states and had the greatest negative impact on imports and the state of Espírito Santo.